2009
DOI: 10.5194/aab-52-343-2009
|View full text |Cite
|
Sign up to set email alerts
|

Selection in the genetic resource: genetic variation of the linear described type traits in the Old Kladrub horse

Abstract: The structure of the breed in 2003 was: 39 sires and 350 dams. The breed was closed against immigration in 1992. In 1993 and 2003 coefficients of inbreeding (Fx) were calculated from 5 parental generations for sires and dams in the whole breed and white and black variety. From 1993 to 2003 decreased the Fx (%) in the breed for stallions from 5.65 to 5.57 and for mares from 7.75 to 4.88. The effective population size was in 1993 Ne=114. 00 and 2003 Ne=140.36. The increment of Ne during the 10-year period was 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 11 publications
6
15
0
Order By: Relevance
“…In the N breed the increase in F x was similar in both sexes. Similar values of F x were estimated by Jakubec et al (2009) in Old Kladrub horses and by Wolc & Balińska (2010) in the Polish Konik population. Sierszchulski et al (2005) found average values of F x =0.88 % in the Polish Arab horse.…”
Section: Methodssupporting
confidence: 80%
“…In the N breed the increase in F x was similar in both sexes. Similar values of F x were estimated by Jakubec et al (2009) in Old Kladrub horses and by Wolc & Balińska (2010) in the Polish Konik population. Sierszchulski et al (2005) found average values of F x =0.88 % in the Polish Arab horse.…”
Section: Methodssupporting
confidence: 80%
“…The average inbreeding coefficient throughout all lines totalled 0.076, with SD of 0.038. This estimated average inbreeding coefficient corresponds to the estimated value of F IT in the molecular part of the analysis (Table 4, F IT = 0.073), as well as the value published by Jakubec et al (2009) in an analysis covering all individuals born in 1993 within the Old Kladruber population (F X = 0.0775).…”
Section: Determining Inter-line Genetic Relationship Using Pedigree Isupporting
confidence: 66%
“…Genetic variability in the Old Kladruber horse lines mentioned above is maintained by breeding schedules when parental pairs are set up from individuals with relationship as small as possible. Thanks to this, there was a reduction in the coefficient of inbreeding in the total population by 2.87%, from 7.75% in horses born in 1993 to the value of 4.88% in those born in 2003 (Jakubec et al, 2009).…”
Section: Determining the Inter-line Relationship Using Microsatellitementioning
confidence: 94%
“…The breed is nowadays included in the genetic resources of the Czech Republic and the population has been fully closed since 2002. As the population is small (effective population size N e = 201), its genetic diversity is continuously monitored (Horin et al 1998;Jakubec et al 2009;Vostry et al 2011;Janova et al 2013). The population is bred in two coat colours -grey (6 sire lines) and black (4 sire lines).…”
Section: Introductionmentioning
confidence: 99%